Librês: diretrizes sobre o uso dessa interlíngua em produtos audiovisuais - SILVA, Sâmia Cristina Martins (2023)
This applied research presents guidelines on the use of the librese interlanguage in subtitles of audiovisual products for deaf people who are not proficient in Portuguese and communicate primarily in Libras. From bibliographic and documentary research, in addition to semi-structured interviews projecives conducted with 26 deaf people, the guidelines below were structured and were in automation through the creation of an artificial intelligence prompt, but not very efficient. This study is based on Brazilian legal premises (Brasil, 2006; 2015) and on discussions about accessibility for deaf people - Araújo, Vieira e Monteiro (2021), Araújo e Alves (2017) e Nascimento (2017) - as well as on aspects involving translation (Pinilla, 2017). As a result, an interlanguage focused on nouns, adjectives, numerals, adverbs, verbs in the infinitive and personal pronouns was created, aiming to build the most objective texts possible and focused on the main information.